1997
DOI: 10.1088/0957-0233/8/11/007
|View full text |Cite
|
Sign up to set email alerts
|

The ESPI measurement of the residual stress distribution in chemically etched cold-rolled metallic sheets

Abstract: A new method for the measurement of residual stresses in sheet materials is presented. The method is based upon the measurement of the curvature resulting from progressive removal of uniform layers from the surface of the specimen by chemical etching. The curvature is obtained from electronic speckle pattern interferograms (ESPI). As an illustration, a thin cold-rolled steel sheet was tested. Surface residual stresses were measured in as-received and heat-treated specimens. Results were found to be within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…The layer removal technique was found to be very sensitive to the curve fitting technique used. Lira et al [8] reported a similar trend and it was shown that a second order polynomial provided the best estimates.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…The layer removal technique was found to be very sensitive to the curve fitting technique used. Lira et al [8] reported a similar trend and it was shown that a second order polynomial provided the best estimates.…”
Section: Resultsmentioning
confidence: 70%
“…The profile traverse length was chosen to be 45 mm based on an error analysis. The subsurface residual stress profile within the specimens was determined using the layer removal technique [7][8][9]. Material was removed incrementally from the treated surface and the resultant change in curvature was used to infer the residual stress distribution.…”
Section: Determination Of Residual Stressmentioning
confidence: 99%
“…where E and n are, respectively, the specimen-elastic modulus and Poisson's ratio and M x (h) and F y (h) are the bending moment per unit thickness and the force per unit thickness in the y-direction after changing the center line by layer removal [2]. By combining Eqs.…”
Section: Article In Pressmentioning
confidence: 99%
“…Residual stress has been assessed using a number of methods: hole drilling, the curvature method, X-ray diffraction, Raman spectrophotometer and neutron diffraction, and magnetic Barkhausen noise (MBN) [1][2][3][4][5][6]. Residual stress has been reported to be related to mechanical properties such as fatigue life, distortion, dimensional stability, and brittle fracture.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous techniques for assessing residual stresses are thus of interest in mechanical and material engineering research, among them destructive tests such as drilling and etching methods [1,2] and nondestructive test (NDT) techniques such as X-ray diffraction, Raman spectrophotometry, ultrasonic testing, neutron diffraction methods, and magnetic Barkhausen noise (MBN) methods [3][4][5][6]. But so far experimental residual stress evaluation has evaluated only average residual stress with unsatisfactory spatial resolution; residual stress fields have been mapped only by numerical simulation techniques such as finite-element analysis (FEA) [7].…”
Section: Introductionmentioning
confidence: 99%